Systemic treatments for breast cancer brain metastasis - Chen, Qiuchi; Xiong, Jie; Ma, Yuxi; Wei, Jielin; Liu, Cuiwei; Zhao, Yanxia (Frontiers in Oncology, 2023)
Breast cancer (BC) is the most common cancer in females and BC brain metastasis (BCBM) is considered as the second most frequent brain metastasis. Although the advanced treatment has significantly prolonged the survival in BC patients, the prognosis of BCBM is still poor. The management of BCBM remains challenging. Systemic treatments are important to maintain control of central nervous system disease and improve patients’ survival. BCBM medical treatment is a rapidly advancing area of research. With the emergence of new targeted drugs, more options are provided for the treatment of BM. This review features currently available BCBM treatment strategies and outlines novel drugs and ongoing clinical trials that may be available in the future. These treatment strategies are discovered to be more efficacious and potent, and present a paradigm shift in the management of BCBMs.